P107 A service evaluation of deep and difficult implant removal services within the Solent NHS Trust: are primary services following FSRH guidelines in respect to Nexplanon removals?. (16th June 2022) - Sekhon, Harmeena; Aziz, Najia; Patel, Rajul
Abstract : Introduction: Nexplanon should be inserted above the fascia and not in the bicipital groove of patients' arms; otherwise, the implant may damage the patient's nearby neurovasculature. The Faculty of Sexual and Reproductive Health (FSRH) guidelines state that a patient's primary point of contact, their General Practitioner (GP) or Sexual Health Service (SHS), should only attempt to remove fully palpable implants. After one failed removal attempt, the patient should be referred immediately to the secondary specialist deep and difficult implant removal (DDIR) service. Therefore, this study aims to compare the characteristics of referrals to the service and to assess the quality of service provided against FSRH guidelines. Methods: A retrospective review of the records of 77 patients who attended the DDIR service at 3 Solent SHSs between September and December 2020 was undertaken. Results: 13% (12/77) of referred implants were inserted at the bicipital groove. Attempts at removal by primary services were against the FSRH guidelines in 27.27% (21/77) of cases. Overall, the services removed 93.5% (72/77) of implants, referred 0.05% (4/77) onwards to plastic surgeons for removal and decided to not remove 0.01% (1/77). Discussion: GPs are inserting implants in the bicipital groove and both GPs and SHSs are attempting to remove implants that they should be referring to the DDIR service immediately. Therefore, these services should receive further training on insertion, removal and referral procedures regarding the implant and further investigation of these services should be undertaken on a larger scale to identify instances when FSRH guidelines are not being followed more accurately.